CSIR - JRF - NET General Aptitude : Theory and Practice - Ajay Kumar (Pathfinder Publication, 2018)
CSIR - JRF - NET General Aptitude : Theory and Practice is a comprehensive book for all undergraduates aspiring for grants from the Council of Scientific & Industrial Research (CSIR) for a Junior Research Fellowship or a Lectureship through the National Eligibility Test. The book covers General Aptitude and takes students through the latest syllabus. It covers puzzles, reasoning, numerical ability, graphical analysis, data interpretation, quantitative comprehension. It incorporates expert explanations, and gives students an edge over the competition by helping them learn through valuable tips and hints to tackle the examination. In addition, the book contains previous years' solved papers so that the students can understand how best to solve the questions in a timely manner. The book is an essential reference for all undergraduates taking up the NET.